Effect of Water Quality, Environmental Quality on Economic Growth in South Sumatra Province 2013-2017 - Dimas Resy Ramadhan; Siti Novia Sari; Syamsurijal A Kadir; Abdul Bashir (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2021)
Environmental problems are currently the most common problems in the Indonesian environment. This environmental problem can be caused by the characteristics of humans as economic beings from several things, ranging from natural factors or factors from humans themselves. Most of these problems sometimes do not have a solution to solve them. So that it causes natural and environmental damage to continue. This study aims to determinethe influence of development on water quality, air quality on economic growth in South Sumatra Province.Secondary data used is time series sourced from the Central Bureau of Statistics, IKPLHD and related agencies during the period 2013 to 2017. The analytical tool used in this study is multiple linear regression based on Ordinary Least Square (OLS) along with statistical tests and tests. Classic Assumptions. The estimation results conducted show that the variables of air quality and water quality have a significant influence and have a positive relationship to per capita economic growth in South Sumatra.